1997
DOI: 10.1021/jp963102d
|View full text |Cite
|
Sign up to set email alerts
|

Chelating Behavior between Metal Ions and EDTA in Sol−Gel Matrix

Abstract: Ethylenediamine tetraacetic acid (EDTA) was encapsulated in a sol-gel-derived optically transparent glass. The complexation of metal cations, Cu(II), Ni(II), Fe(III), Cr(III), Co(II), Mn(II), Pd(II), and Ir(IV), with EDTA in solutions and in gels was evidenced by the formation of individual colors. A comparison of the absorption spectra of M n+ /EDTA in solution, M n+ /EDTA in gel, and M n+ /EDTA complex in gel was performed. The results show that (i) all six chelating sites in EDTA remain active in a sol-gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 9 publications
3
39
0
Order By: Relevance
“…Contrary of the citric acid the "constant region" begins at = 0.25. EDTA forms the complexes with metal ions usually in molar ratio 1:1, independently on its valence [28], but formation of the binuclear Cu-EDTA complexes in ratio 2:1 was also published [29]. Our results indicates that the change of slope in the concentrations dependence of U corresponds with the ratio one copper(II) ion and four functional groups (which is ratio Cu:EDTA = 1:1).…”
Section: Resultssupporting
confidence: 65%
“…Contrary of the citric acid the "constant region" begins at = 0.25. EDTA forms the complexes with metal ions usually in molar ratio 1:1, independently on its valence [28], but formation of the binuclear Cu-EDTA complexes in ratio 2:1 was also published [29]. Our results indicates that the change of slope in the concentrations dependence of U corresponds with the ratio one copper(II) ion and four functional groups (which is ratio Cu:EDTA = 1:1).…”
Section: Resultssupporting
confidence: 65%
“…The significantly lower yields of DMSP hydrolysis observed for both treatments A and B compared with the levels measured in treatment C suggested that one of the reagents present in the DMSOr cocktail (DMSOr itself, ethylenediaminetetraacetic acid [EDTA] or flavine mononucleotide [FMN]) might have hampered the reaction of DMSP hydrolysis by OH -. Because DMSP is a zwitterion (i.e., an electrically neutral molecule bearing formal unit electrical charges of opposite sign on different atoms), interaction with EDTA, which is a well-known chelating agent (Zaitoun and Lin 1997) was plausible. EDTA could make DMSP partially unavailable for hydrolysis by OH -by interacting with DMSP at the level of the sulfur atom bearing a positive charge.…”
Section: Discussionmentioning
confidence: 99%
“…According to the theoretical background [42], it is known that formation constant (K f ) of chelated Ni(EDTA) 2− complex anion from free Ni 2+ ion and EDTA 4− ion is 10 18.4 (Eqs. (3) and (4)).…”
Section: Edta-assisted Impregnation Methodsmentioning
confidence: 99%